Socioeconomic drivers of application of nitrates as a curing agent in skinless longganisa processed meat products sold in Bankerohan public market in Davao City, Philippines - Lorilla, Aaron P.; Guiral, King Louiegie G.; Matullano, Kathleen R.; Sarmiento, Jon Marx P.; Alviola, Pedro A.; Obsioma, Virginia P.; Tagubase, Jackie Lou J. (2019)
The application of nitrite in processed meat has remained crucial in meat production. Not only does it preserve meat by inhibiting rancidity and bacterial growth, but it also enhances the aroma, flavor, color, and texture of the meat. However, the crucial part lies on how meat processors follow food safety protocols and meat processing standards.
Overapplication will increase the carcinogenicity while underapplication will be insufficient to inhibit bacterial growth. Hence, this study was conducted to determine if linkages exist in the food safety attributes and the socioeconomic factors of the meat seller/processors in Bankerohan Public Market in Davao City and the residual nitrite levels of the longganisa products. Using a random effects panel data model, the main objective of the study was to assess how household sociodemographic and economic factors impact the meat seller/processors' application of nitrite in their longganisa products. The results show that the effect on nitrite application is negatively associated with household income, household size, and educational attainment and is positively associated with the number of children, marital status, and number of years in longganisa selling. Thus, monitoring and training, especially in key intervention points such as license renewal for meat sellers, should emphasize the benefits of applying the right amount nitrites as a crucial food safety measure.
Keywords: Mindanao studies; Longganisa